Dietary inflammatory index and non-alcoholic fatty liver disease risk: a systematic review and meta-analysis of observational studies - Amirkalali, Bahareh; Farahmand, Mohammad; Rashedi, Minoo Hasan; Gholami, Ali; Sheikholmolooki, Fateme; Sedighi, Mohadeseh; Doustmohammadian, Azam (Frontiers in Nutrition, 2025)
AimChronic inflammation plays a significant role in the progression of non-alcoholic fatty liver disease (NAFLD). Adopting an anti-inflammatory diet can help prevent or mitigate NAFLD and its associated complications. This meta-analysis builds on previous research by examining the association between the Dietary Inflammatory Index (DII) and NAFLD risk, incorporating additional studies and employing rigorous evidence assessment.MethodsWe systematically searched major databases (Cochrane Library, PubMed, Web of Science, and Scopus) from inception to June 2024 for English-language observational studies examining the association between DII and NAFLD prevalence. Pooled odds ratios (ORs) or hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated using random-effects models for studies with significant heterogeneity; otherwise, fixed-effects models were applied. Subgroup analyses were conducted to explore heterogeneity based on body mass index (BMI), DII definition, sample size, geographical region, age, and NAFLD diagnostic criteria. Evidence certainty was assessed using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) framework. The study was registered in PROSPERO (CRD42023430798).ResultsEleven studies (9 cross-sectional with 14 effect sizes and 2 cohort with 2 effect sizes) were analyzed. Higher DII scores were significantly associated with increased NAFLD risk, with a pooled OR of 1.56 (95% CI: 1.24–1.95; p < 0.001) in cross-sectional studies and an HR of 0.21 (95% CI: 0.12–0.30; p < 0.0001) in cohort studies. Subgroup analyses confirmed consistency across BMI ≥ 25, energy-adjusted DII or DII, studies in Asia and Europe, and participants <46 years, with reduced heterogeneity (I2 < 50%) in these categories. GRADE rated the certainty of evidence as “very low.”ConclusionAnti-inflammatory diets can reduce NAFLD risk. However, high-quality studies are needed to confirm this association.